Kultura ma znaczenie – implikacje dla strategii budowania rzeczywistości wychowawczej i kultury pedagogicznej - Tomkowiak, Hubert (Kultura-Społeczeństwo-Edukacja, 2021)
The considerations presented are an attempt to search for analogies between the influence of culture on the wellbeing of nations and the influence of pedagogical culture on the well-being of growing up generations. Raising the level of pedagogical culture, especially of parents, should be an important task of the Polish school. A somewhat forgotten tool for its realization is the pedagogization of parents, the rank of which should be systemically raised to a level ensuring its universal application. Therefore there is a need for a new, educational paradigm of school.